Understanding women experiences and decision making in choosing birthplace - Ismail, Farah Raihana; Hashim, Haslinda; Raja Yusof, Raja Nerina (IJABM, 2016)
Understanding consumer behaviour pertaining to healthcare consumption is vital in assessing and improving the service quality. Maternity care is one the largest division that most of the healthcare provider holds within the community of healthcare market and childbirth is most common reported cases. Choosing the ideal birthplace is one of the pivotal decision in childbirth process and the decision made are influences by different attributes. Understanding women’s experiences during the childbirth process provide useful insights on how experiences influence the decision made. Intense competition and lucrative industry required healthcare provider to further understand the consumer need and demand as well focusing more towards customer-centred strategy.Purpose of this article is to discuss and review the relevant literature regarding the childbirth experiences and birthplace choice phenomenon from the lenses of consumer.